Using Spectroscopic Techniques in Classifying the Land in Basrah Province - Ali Saleh Hussein Al Lawy, Researcher. Ola; Abdullwahab Hassan Al-Assady , Prof. Dr. Mohammed (Basra studies journal, 2023)
The spectral indicators and clues used in the study, which were represented by (NDVI vegetative index, NDWI water index, channel guide index BR, sabkhat moisture index HUE index, soil salinity index and salinity index, and mineral compounds index) are among the most important processes of spectral treatments for detecting the land cover using mathematical operations on certain spectral areas on which remote sensing studies and geographic information systems depend, then they will be used in classifying the land cover of Basra Governorate by adopting the Andersen classification of the US Survey Authority, and calculating the area of each type of this cover and revealing the changes that occurred during the period confined between the year (1980-2000-2020) AD. In order to determine their spatial suitability for investment, as well as identifying the most important sites in the governorate to draw plans and prepare them for spatial development by virtue of its geographical location and its possession of many sources of natural resources capable of investment